Security dimensions of climate change adaptation - Bruin, Sophie Pieternel de (Edward Elgar Publishing, 2013)
This timely Research Handbook discusses the challenges brought about by the need to adapt to a changing climate. It considers how adaptation is necessary to address impacts resulting from the warming of the Earth's atmosphere which is already unavoidable due to past emissions.